Evaluation of soybean genotypes (Glycine max (L.) Merril) at Jaboticabal country (S. Paulo State, Brazil) conditions - Pípolo, Valéria Carpentieri; Athayde, Manuel Luis Ferreira; Pípolo, Antonio Eduardo (Semina: Ciências Agrárias, 1993)
<!--[if gte mso 9]> Normal 0 21 MicrosoftInternetExplorer4 <![endif]--><!--[if !mso]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:Verdana; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:536871559 0 0 0 415 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman";} @page Section1 {size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:35.4pt; mso-footer-margin:35.4pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> An experiment involving 27 soybean genotypes was sowed at the Agriculture College of Jaboticabal - UNESP, on november 24th, 1988. The experimental plots were arranged in a randomized complete bloc'design with three replications and located in a area of dark red latosoil distrofic, of overage texture and fertilirty. The objetive was to, select short cycle soybean genotypes shownig adequate agronomic characteristics to sow in sugar cane renewal areas. 'Cometa' and 'Paraná' were the earliest genotypes with a cycle of 97 and 100 days respectively, the latest were 'Santa Rosa'and Ft-11 (140 days), FT 80-25158 and FT 80-25372 (126 days), FT 80-30736 and FT Bandeirantes (122 days); the others genotypes showed cycles between 100 to 120 days. All the genotypes yielded more genotype than 2400 kg/ha with exception of 'Cometa' cultivar (1.693 kg/ha). Genotype FT 81-3793 did not show adequate vegetative development with a final plant height of 47.13cm and first pod insertion height of 10.52cm.